From prioritization to implementation: updating the PARC WP5 project portfolio through the second prioritization round - Garcia Arenas, Celia; Aiello Holden, Kiara; Svingen, Terje; Knapen, Dries; Kerdine-Römer, Saadia; Lindeman, Birgitte; Smith, Nicola M.; Le Hegarat, Ludovic; Vanhaecke, Tamara; Rivière, Gilles; Marx-Stoelting, Philip (Frontiers in Toxicology, 2026)
The Partnership for the Assessment of Risks from Chemicals (PARC) represents a joint effort among risk assessors, regulatory authorities, and the scientific community to advance the implementation of next-generation risk assessment (NGRA) in line with the objectives of the EU Chemicals Strategy for Sustainability. Addressing the challenges faced by the national and European regulators by integrating data generated through innovative methodologies is central to achieving this goal. Following an initial phase of the partnership, in which projects were defined based on a first prioritization of methodologies, a second prioritization round was conducted with input from the Governing Board representatives of all participating entities. This second process also considered the Key Areas of Regulatory Challenge introduced by the European Chemicals Agency in 2023, ensuring that the evolving research agenda within PARC is closely aligned with current and future regulatory needs. As a result, WP5 Hazard Assessment has updated its project portfolio to include four new projects that bridge identified regulatory gaps and strengthen the implementation phase of PARC. One project focuses on developmental and reproductive toxicity, another on developmental immunotoxicity, a third explores sexual dimorphism associated with hepatotoxicity, and a fourth transversal project, Regulatory Readiness of NAMs, aims to accelerate the regulatory uptake of promising methods developed under Work Package 5 (WP5). This article complements the previous PARC special issue by providing an overview of the updated WP5 project portfolio, illustrating the progression from prioritization to implementation, and highlighting how these new projects respond to evolving regulatory needs and contribute to the effective integration of new approach methodologies (NAMs) into chemical risk assessment.